Immobilization of sulfates and heavy metals in gold mine tailings by sodium silicate and hydrated lime. Issue 5 (October 2018) - Kiventerä, Jenni; Sreenivasan, Harisankar; Cheeseman, Christopher; Kinnunen, Paivo; Illikainen, Mirja
Highlights: Alkali activation of gold mine tailings with NaOH/Na2 SiO3 and Ca(OH)2 . High Immobilization of sulfates and arsenic were achieved with hydrated lime. The compressive strength of all samples were suitable for mine backfilling. Abstract: Gold mining produces hazardous tailings wastes with elevated sulfur content and high levels of heavy metals including oxyanion elements such as V and As. This research investigated activation of these tailings with calcium hydroxide and sodium hydroxide/sodium silicate as a way to stabilize the material and limit leaching of harmful components. The effects of thermal treatment on the reactivity of the tailings and the use of different activating solutions on the physical properties, microstructure and leaching of harmful components are reported. The effect of adding ground granulated blast furnace slag to the tailings is also assessed. The use of 5 wt % Ca(OH)2 activating solution produces optimum performance increasing the immobilization efficiency of sulfates, arsenic and the other harmful elements. Heat-treating mine tailings at 900 °C slightly improves the reactivity but did not improved the immobilization efficiency. Microstructural analysis by TEM and XRD confirmed that stabilization is based on calcium sulfate and/or ettringite formation during alkali-activation. All materials achieved reasonable compressive strength after 28 days of curing and the potential for using alkali activation as a method to treat tailings from mining is discussed.